A Human-Centred approach to e-Agricultural systems. Issue 24 (2015) - Somers, Sinead O'Neill; Stapleton, Larry
Abstract: Within business enterprises farmers lags behind in the uptake of new information technologies for the control and automation of farming systems. In spite of decades of research into technology acceptance we still do not have a good understanding as to why this is the case. IT adoption in agricultural communities is perceived to be increasingly important by policy makers as a means of adapting to changes within agriculture. This paper proposes preliminary findings to validate a new systems framework of e- Agriculture adoption and innovation that will open new avenues of research for control and automation systems theory and practice informing policy in respect of e-readiness of rural communities.